2017
DOI: 10.1016/j.msec.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of poly(lactic-co-glycolic acid) and poly( dl -lactide-co-ε-caprolactone) electrospun fibers for the treatment of HSV-2 infection

Abstract: More diverse multipurpose prevention technologies are urgently needed to provide localized, topical pre-exposure prophylaxis against sexually transmitted infections (STIs). In this work, we established the foundation for a multipurpose platform, in the form of polymeric electrospun fibers (EFs), to physicochemically treat herpes simplex virus 2 (HSV-2) infection. To initiate this study, we fabricated different formulations of poly(lactic-co-glycolic acid) (PLGA) and poly(DL-lactide-co-ε-caprolactone) (PLCL) EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Despite both HFIP and TFE sharing many characteristics such as high polarity and similar molecular structure, there are several key differences that may impact fiber properties. As previously described [35], TFE has a higher dielectric constant (26.1 F/m) compared to HFIP (16.7 F/m) [57]. This increased charge capacity may confer additional instability to TFE solvents during electrospinning, requiring more polymer to produce well-defined fiber morphology [58].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite both HFIP and TFE sharing many characteristics such as high polarity and similar molecular structure, there are several key differences that may impact fiber properties. As previously described [35], TFE has a higher dielectric constant (26.1 F/m) compared to HFIP (16.7 F/m) [57]. This increased charge capacity may confer additional instability to TFE solvents during electrospinning, requiring more polymer to produce well-defined fiber morphology [58].…”
Section: Discussionmentioning
confidence: 98%
“…For blank EFs, 15–20% PLGA w/w and 12–20% PLCL w/w were dissolved in either 3 mL TFE or HFIP solvent overnight while shaking at 37°C. The following day, 2 mL of PLGA or PLCL solution was aspirated into, and electrospun from, a 3 mL plastic syringe as previously described [26, 35]. All formulations were electrospun with a flow rate of 2.0 mL/hr and an applied voltage of 20 kV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avidin palmitate was synthesized for conjugation to NPs as previously described. 15,16,18,19 Briefly, 40 mg avidin (A9275, Sigma-Aldrich Corp., St. Louis, MO, USA) was dissolved in 4.8 mL 2% sodium deoxycholate (NaDC) in phosphate-buffered saline (PBS) warmed to 378C. Palmitic acid-NHS (PA-NHS, Sigma-Aldrich Corp.) was dissolved in 2% NaDC to a final concentration of 1 mg/mL and sonicated until well-mixed.…”
Section: Synthesis Of Avidin Palmitate Conjugatesmentioning
confidence: 99%
“…These formulations achieved both burst- and sustained-release of all three compounds in vitro , and MVC and AZT eluted from the fibers were found to maintain antiviral activity against HIV-1 BaL, while activity of eluted acyclovir was not tested. However, Aniagyei et al have shown release of ACV from poly (lactic-co-glycolic) acid (PLGA) and poly(lactide-co-caprolactone) (PLCL) over the course of 28 days, and observed complete viral inhibition with eluted doses of 1–200 μg/mL [47]. Carson et al showed programmable release of tenofovir (TFV), AZT, MVC and raltegravir (RAL) from fibers composed of blends of poly(lactic-co-glycolic) acid (PLGA) and polycaprolactone (PCL) [48].…”
Section: Electrospun Fibers For Female Reproductive Challenges: Cumentioning
confidence: 99%